Functional Role of Long-Chain Acyl-CoA Synthetases in Plant Development and Stress Responses - Zhao, Huayan; Kosma, Dylan K.; Lü, Shiyou (Frontiers in Plant Science, 2021)
Fatty acids (FAs) play vital roles in plants as components of lipid membranes that demarcate cells and organelles, as sources of stored energy in the form of neutral lipids, and as signaling molecules that elicit plant responses to adverse conditions. The activation of FAs through the formation of acyl CoA intermediates by acyl CoA synthetase (ACS) family enzymes is required for their synthesis and degradation. Long chain acyl CoA synthetases (LACS) represent a small subgroup of ACS enzymes that specifically convert long chain or very long chain fatty acids into corresponding thioesters for multiple lipid-associated processes. Alteration of LACS activity often results in pleiotropic phenotypes such as male sterility, organ fusion, aberrant cuticular structure, delayed seed germination, altered seed oil content as well as plant capacity to respond to various environmental stresses. This review provides a comprehensive analysis of LACS family enzymes including substrate specificity, tissue specific expression patterns, and distinct subcellular localization highlighting their specific roles in lipid synthesis and degradation, the effects of altered LACS activity on plant development, the relationship between LACS activity and stress resistance as well as the regulation of LACS activity. Finally, we pose several major questions to be addressed, which would advance our current understanding of LACS function in plants.